A Manifestation of Climate Change? A Look at Typhoon Yolanda in Relation to the Historical Tropical Cyclone Archive - David, Carlos Primo C.; Racoma, Bernard Alan B.; Gonzales, Jonathan; Clutario, Mark Vincent (Science Diliman: A Journal of Pure and Applied Sciences; Vol 25 No 2 (2013))
The IBTRACS world database of tropical cyclone(TC) tracks was analysed to determine potential historical trends in TC characteristics for the west Pacif ic basin. Trends are then related to the characteristics of Typhoon Yolanda to see if this individual event constitutes as a data outlier or is part of a trend that can be related to climate change. In terms of TC frequency, it is deduced that there is a decreasing pattern in tropical cyclone formation starting in 1970. It is also noted that while there is no trend observed in the annual mean maximum wind speed, a decrease in the number of high wind speed TCs is measured for the months of November and December. The location of TC formation has also been changing towards a higher latitude but closer to the Philippines in terms of longitude. Lastly, typhoons making landfall in the Visayas and Mindanao region have also become slightly more frequent in the last decade. Except for the last f inding, the 2013 typhoon season does not f it in these general trends. This year may be the start of a new trend or shift in TC characteristics (which we will only know after a few more years) but is most likely part of the inherent annual variability of typhoon characteristics. Yolanda goes against perceived trends but its occurrence signif ies that there is still much to learn about tropical cyclones and the impending impacts of climate change in general.